Role of Financial Inclusion in Economic Growth in Brazil - Souza, Clara (International Journal of Finance, 2025)
Purpose: The purpose of this article was to analyze role of financial inclusion in economic growth in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Financial inclusion plays a crucial role in driving economic growth in Brazil by improving access to banking, credit, and financial services, particularly in underserved areas. Studies show that increased financial inclusion helps reduce income inequality, boosts entrepreneurship, and stimulates business expansion, particularly for small and medium-sized enterprises (SMEs). Mobile banking, microfinance, and digital financial services have proven effective in reaching rural populations and fostering economic participation. However, challenges such as regional disparities, limited digital infrastructure, and financial literacy remain. Addressing these barriers through targeted policies, investment in digital banking, and financial education can significantly enhance economic growth and reduce poverty in Brazil. Unique Contribution to Theory, Practice and Policy: The theory of financial intermediation, theories of inclusive growth & modernization theory may be used to anchor future studies on the role of financial inclusion in economic growth in Brazil. In practice, financial institutions in Brazil should prioritize the development of user-friendly and accessible financial products that cater to underserved populations, particularly in rural and remote areas. Policymakers should also prioritize expanding financial education initiatives across the country, integrating financial literacy into the national education curriculum, and providing incentives for financial institutions to offer services to underserved and rural populations.